Residual cyclooxygenase-1 activity and epinephrine reduce the antiplatelet effect of aspirin in patients with acute myocardial infarction - Moscardó, Antonio; Santos, María Teresa; Fuset, María Paz; Ruano, Miguel; Vallés, Juana (Thrombosis and Haemostasis, 2011)
Aspirin treatment is essential in patients with acute myocardial infarction (AMI) to block platelet thromboxane (TXA)2 synthesis. Epinephrine is known to enhance platelet reactivity induced by other agonists and to be elevated in patients with AMI due to stress. Our objective was to study the influence of epinephrine on platelet TXA2 synthesis in patients treated with aspirin for AMI at early onset (within 48 hours) and the potential biochemical mechanisms involved in the functional response. Washed platelets from 45 patients with AMI and 10 aspirin-free controls were stimulated with arachidonic acid (AA) or AA + epinephrine, and aggregation and TXA2 synthesis were evaluated. Full platelet aggregation was recorded in 8/45 patients (18%) with a partial TXA2 inhibition (86%) vs. the aspirin-free controls. Platelets from the remaining 37 patients did not aggregate to AA and had TXA2 inhibition >95%. However, when platelets were simultaneously stimulated with AA + epinephrine, in 25/37 patients a large intensity of aggregation (73%) was observed and a 5.5-fold increase in TXA2 synthesis, although this remained residual (<5% of aspirin-free controls). This residual-TXA2 was critical in the functional response, as demonstrated by the complete inhibition by TXA2 receptor blockade or additional aspirin in vitro. The phosphatidylinositol-3-kinase activity and the cytosolic calcium levels participated in this platelet response elicited by a receptor cooperation mechanism, while the Rho/p160ROCK pathway or the blockade of the ADP receptors (P2Y1, P2Y12) were without effect. Residual-cyclooxygenase –1 activity and epinephrine enhance TXA2-dependent platelet function, which may reduce the clinical benefit of aspirin in patients with AMI.
Keywords: Platelets; aspirin; thromboxane A2; epinephrine; acute myocardial infarction